Integração de ia para monitoramento de dados em linha de produção - ALMEIDA, Kauâ Bento Aguiar de; MOIO, Thalles Melo; LIMA, Vitor Fernandes (126, 2025)
Este trabalho tem como objetivo a aplicação de uma solução de monitoramento e tratamento de dados, construído sob a metodologia Design Science Research (DSR), visando acompanhar continuamente o funcionamento dos sensores instalados. A organização do trabalho contempla uma análise teórica sobre as revoluções industriais, monitoramento de dados através de IA, softwares de desenvolvimento. Para a demonstração, foi simulada uma linha de produção utilizando Factory I/O e Codesys (OPC UA). Os dados operacionais foram coletados via Python e persistidos em um banco de dados SQLite. O diagnóstico do sistema é realizado em duas etapas: o modelo Naive Bayes classifica a probabilidade de falha, e a integração com a API do ChatGPT (IA Generativa) atuando como assistente de diagnóstico, gerando relatórios periódicos de MTBF, MTTR e o Diagrama de Ishikawa para identificação automatizada da causa raiz. A avaliação do artefato DSR comprova sua utilidade na tradução de dados brutos em ações de manutenção prescritiva assertiva, superando as limitações dos métodos reativos tradicionais.

This work aims to apply a data monitoring solution. To ensure the simulation is realistic, a prototype of an industrial area for parts separation will be used, aiming to continuously monitor the operation of the installed sensors. For data communication, the Factory.Io simulation software was 2 used, communicating via OPC with Codesys. The collected data will be sent to Microsoft VS Code, which will execute Python code to communicate with Codesys Win V3 and the Chat GPT Plus API. It will then process digital and analog data, which will be analyzed using AI to generate periodic reports on Downtime, MTBF, and MTTR, performing Ishikawa diagrams to identify the root cause. This will contribute to the implementation of assertive predictive and prescriptive maintenance. This research highlights how data monitoring enables the instant capture and analysis of equipment information, facilitating maintenance actions. The development of this study included a detailed literature review, addressing the main concepts related to the topic. The work is organized with a theoretical analysis of industrial revolutions, data monitoring through AI, and software development. The results show that the combination of industrial automation and AI techniques significantly contributes to fault detection, operational optimization, and decision-making support. The study demonstrates the feasibility of a scalable solution with didactic application and potential for real industrial environments. Keywords.
Keywords: Controle de processos; Automação industrial; Controle e Processos Industriais